Measurement of erythrocyte lifespan using a CO breath test in patients with thalassemia and the impact of treatment - xiaolin yin; Jingting Luo (Mediterranean Journal of Hematology and Infectious Diseases, 2023)
Background: Thalassemia comprises a diverse group of genetic disorders that affects the synthesis of globin chains, with a global distribution. The use of erythrocyte lifespan (ELS) to assess differences among patients with different types of thalassemia and the efficacy of splenectomy has not been implemented.